PEMANFAATAN VIDEO YOUTUBE SEBAGAI MEDIA PEMBELAJARAN FIKIH PADA MATERI SHALAT (Studi Kasus di SD Islam Bekasi) - Tazkiatunnisa, Sarah (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This research is motivated by the issues encountered by students during the learning process of prayer material in Islamic Elementary School Bekasi, where many students feel bored in class. To address the boredom in learning, especially in the practical aspects of prayer material, an innovative learning approach is required by utilizing YouTube videos. This research aims to describe the utilization of YouTube videos as a learning media for the fiqh subject on prayer material for the second-grade class at Islamic Elementary School in Bekasi and to identify the obstacles faced in utilizing YouTube videos. This research uses a qualitative approach with a case study method. The data collection techniques used in this research are observation, interview, and documentation. The results show that the utilization of YouTube videos as a learning media for the fiqh subject on prayer material implemented in the class consists of three stages: planning the learning, implementing the learning, and evaluating the learning. The utilization of YouTube videos as a learning media for the fiqh subject on prayer material is proven to be effective. This is indicated by the students' enthusiasm and the absence of students falling asleep during the learning process. The obstacles in the learning process include: firstly, infrastructure aspects covering wifi/network factors, PLN electricity supply, and the limitation of projectors/infocus. Secondly, the students' attitude aspect, with a small number of them still requiring more motivation to learn.